Analisis Hubungan Resiliensi Matematik Terhadap Kemampuan Pemecahan Masalah Siswa Pada Materi Lingkaran - Sri Maharani; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this study to determine the relationship of mathematical resilience to students problem solving abilities. This research was conducted in MTs Negeri Kota Cimahi class VIII-I even semester in academic year 2017-2018. The method used is qualitative descriptive method. Population taken is all students of class VIII MTs Negeri Kota Cimahi. Sampling using purposive sampling technique, which is a determination and sampling technique determined by the researchers with certain considerations. The sample consists of 34 students. Circle material used in research. Research instrument as many as 5 items about problem solving and resilience statement scale as many as 40 statement. The conclusion gained is that there are difficulties experienced by students in solving problem solving problem and there is correlation between mathematical resiliency to student problem solving ability equal to 0,649.